TANTANGAN MORAL DALAM ERA AI BAGI PEMBELAJARAN PAI - Nur Mutiah; Maya Ramadani; Dela Indah Saputri; Hengki Satrisno; Bambang Irawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The rapid growth of Artificial Intelligence (AI) has brought significant changes to educational practices, including Islamic Religious Education (PAI). While AI offers opportunities for personalized learning, accelerated information access, and improved instructional efficiency, it also introduces serious moral and spiritual challenges for students. This study aims to analyze how AI influences students’ ethical behavior, spiritual formation, and learning integrity. Using a qualitative approach with a library research design, this study examines scholarly articles, books, and international reports published between 2020 and 2024, focusing on themes related to AI ethics, digital morality, and Islamic education. Content analysis was used to identify patterns concerning moral risks such as plagiarism, academic dishonesty, dependency on AI, and reduced critical thinking; as well as spiritual implications including superficial religiosity, declining contemplation, and weakened internalization of Islamic values. The findings reveal that AI reshapes students’ learning behaviors and spiritual habits, requiring Islamic education to adapt through ethical digital literacy, reflective learning, and the strengthening of Islamic moral values. This study concludes that AI should not be positioned merely as a threat, but as a tool that needs wise, ethical, and value-based guidance. Effective PAI learning in the AI era requires pedagogical adaptation, moral reinforcement, and a comprehensive strategy to preserve students’ integrity and spiritual awareness.